2017
DOI: 10.14715/cmb/2017.63.10.21
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 secreted by oral cancer- associated fibroblast accelerated VEGF expression in tumor and stroma cells

Abstract: Oral cancer represents the sixth most common cancer type worldwide. Patients with oral cancer express high levels of IL-6 which is associated with very poor prognosis. Previous studies illustrated that IL-6 cytokine induces angiogenesis. It has also been reported that the presence of Cancer- Associated Fibroblasts (CAFs) is essential for angiogenesis. In this study, we examined the correlation between IL-6 and CAF and the role of this correlation on VEGF production. In this study, quantitative expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In this research, expression of VEGF protein in the cells was confirmed by the immunofluorescence study, previously described by Mirkeshavarz et al 19 The cells were fixed in 10% paraformaldehyde for 30 minutes at room temperature. After that, the cells were washed with PBS and blocked in 2% bovine serum albumin (BSA) at room temperature.…”
Section: Vegf Protein Expression In Cellsmentioning
confidence: 87%
“…In this research, expression of VEGF protein in the cells was confirmed by the immunofluorescence study, previously described by Mirkeshavarz et al 19 The cells were fixed in 10% paraformaldehyde for 30 minutes at room temperature. After that, the cells were washed with PBS and blocked in 2% bovine serum albumin (BSA) at room temperature.…”
Section: Vegf Protein Expression In Cellsmentioning
confidence: 87%
“…IL-6 is also a representative marker of clinical correlation and a common prognostic factor in patients with cancer. 25 Various studies have suggested that IL-6 is important in cervical carcinogenesis because it is a central pro-inflammatory cytokine involved in female genital infection and is abundant in the microenvironment of cervical cancer. 26 Moreover, the association of IL-6 with angiogenesis has been reported to depend on its ability to induce the production of VEGF, a potent angiogenic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of chick embryo extract causes a considerable increase in the content of serum IL-1ß and IL-6, plays an important role in stimulation of hematopoiesis and provides a basis to consider this substance as an immunomodulator in pathologic immunosuppresive states [ 16 ]. Previous study illustrated that IL-6 cytokine induces angiogenesis [ 32 ]. The recently, more attentions have been given to the close relationship between tissue regeneration and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%